Impact of Food Restriction on the Expression of the Adiponectin System and Genes in the Hypothalamic–Pituitary–Ovarian Axis of Pre‐Pubertal Ewes. (13th July 2016) - Wang, R; Kuang, M; Nie, H; Bai, W; Sun, L; Wang, F; Mao, D; Wang, Z
Contents: Adiponectin, a cytokine secreted typically by adipocytes, has been implicated as a molecular switch between female reproduction and energy balance. The present study was undertaken to investigate the expression of adiponectin system and patterns of genes in the hypothalamic–pituitary–ovary (HPO) axis of food‐restricted pre‐pubertal ewes. Eighteen 2‐month‐old female ewes were assigned to 3 groups after a pre‐feeding ad libitum for 10 days (six in each group): the control group (C), the low‐food‐restricted group (LR) and the high‐food‐restricted group (HR), which were fed with 100%, 70% and 50% of ad libitum food intake, respectively. The hypothalamus, pituitary, ovary and serum were collected after food restriction for 2 months. Results by ELISA showed that food restriction increased serum adiponectin concentrations. Quantitative real‐time PCR showed that the gene transcriptions for adiponectin receptor 1 (AdipoR1) and 2 (AdipoR2) were enhanced in the hypothalamic–pituitary–ovarian (HPO) axis, while KISS‐1 / GPR‐54 and gonadotropin‐releasing hormone (GnRH) in the hypothalamus and luteinizing hormone β‐subunit (LHβ) and follicle‐stimulating hormone β‐subunit (FSHβ) in the pituitary were reduced after food restriction. Immunohistochemistry results demonstrated that AdipoR1 localized in the oocytes of follicles in the ovary. These results suggest that the alterations in the expression of adiponectin and its receptors in response to food restriction might negatively influence the HPO axis.